FATIGUE LIFE ANALYSIS OF SHAFTING-YOKE IN GEARBOX - CHEN Ping; FANG Jie; ZHOU Zhi; XU Xing; ZHANG JingTong (Jixie qiangdu)
As one of the crucial components of the gearbox in the car,the Shafting-Yoke’s fatigue life directly affects the performance of the gearbox. The Shafting-Yoke of the manual transmission is taken as the research object,which adopting finite element software to analysis its fatigue stress and employing the dynamic simulation software to obtain its load spectrum. A method combining based on GL code predicting material S-N curve and Goodman mean stress correction was developed to calculate the fatigue life of Shafting-Yoke. The fatigue test of Shafting-Yoke shows that the location of damage and the fatigue life of ShaftingYoke of computer simulation and protracted-test are basically same,which proves the reliability and practicability of method promoted in this paper,it can play a guiding role for structure design and optimization of Shafting-Yoke.